AB0572 Additional Role of FDG Pet/Ct in the Assessment of Disease Activity in Takayasu Arteritis. (10th June 2014) - Tombetti, E.; Incerti, E.; Salerno, A.; Sartorelli, S.; Di Chio, M.C.; Alongi, P.; Fallanca, F.; Papa, M.; Gianolli, L.; Sabbadini, M.G.; Manfredi, A.A.; Picchio, M.; et al.
Abstract : Background: Takayasu arteritis (TA) is an inflammatory vasculitis, typically affecting young women with important morbidity and mortality and a largely unknown pathogenesis. Disease activity (DA) evaluation is still a major unresolved issue, currently defined according to NIH criteria. Objectives: Evaluation of the additional role of PET/CT with FDG (PET/CT) in the assessment of DA status. Methods: A cross-sectional analysis of 19 patients (pts) with definite TA was performed. DA was evaluated with NIH criteria, and all pts underwent PET/CT and magnetic resonance angiography (MRA) examinations, with a median interval of 60 days. All vascular lesions uptake in PET/CT was evaluated both with a qualitative and a quantitative (SUV max) method. The capability of MRA and PET/CT in detecting active vascular inflammation was compared in all the lesions evaluable for dimensions with PET/CT. DA as assessed by MRA and PET/CT was compared with DA by NIH criteria. Results: In 11/19 pts PET/CT was positive with a median SUVmax of 3.5 (range: 2.7-9.8). Of the 89 vascular lesions evidenced by MRI and evaluable with PET/CT, 24 (27%) showed a positive uptake. Three out of 6 pts with active disease at the time of MRA showed vascular enhancement in at least one lesion, while vascular enhancement was observed in 4/13 pts with inactive disease. Two out of 5 pts with active disease at the time of PET/CT showed vascular uptake in at least one vascular lesion, while vascular uptake was observed 9/14 pts with inactive disease. Five out of 11 pts with evidence of uptake on PET/CT showed vascular enhancement at MRI, while 3/8 pts with a negative PET/CT showed vascular enhancement at MRI. Conclusions: NIH criteria, MRI, and PET/CT are non-redundant modalities of addressing DA in TA, possibly giving complementary information. Prospective evaluation of these preliminary results is needed to define the precise role of a multi-modality assessment of DA in TA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5497